New vistas on cannabis use disorder. (15th September 2017) - Melis, Miriam; Frau, Roberto; Kalivas, Peter W.; Spencer, Sade; Chioma, Vivian; Zamberletti, Erica; Rubino, Tiziana; Parolaro, Daniela
Abstract: Cannabis sativa preparations are the most consumed illicit drugs for recreational purposes worldwide, and the number of people seeking treatment for cannabis use disorder has dramatically increased in the last decades. Due to the recent decriminalization or legalization of cannabis use in the Western Countries, we may predict that the number of people suffering from cannabis use disorder will increase. Despite the increasing number of cannabis studies over the past two decades, we have gaps of scientific knowledge pertaining to the neurobiological consequences of long-term cannabis use. Moreover, no specific treatments for cannabis use disorders are currently available. In this review, we explore new research that may help fill these gaps. We discuss and provide a solution to the experimental limitation of a lack of rodent models of THC self-administration, and the importance this model can play in understanding the neurobiology of relapse and in providing a biological rationale for potential therapeutic targets. We also focus our attention on glial cells, commenting on recent preclinical evidence suggesting that alterations in microglia and astrocytes might contribute to the detrimental effects associated with cannabis abuse. Finally, due to the worrisome prevalence rates of cannabis use during pregnancy, we highlight the associations between cannabis use disorders during pregnancy and congenital disorders, describing the possible neuronal basis of vulnerability at molecular and circuit level. This article is part of the Special Issue entitled "A New Dawn in Cannabinoid Neurobiology". Highlights: A new relapse model of context- and cue-induced marijuana seeking is proposed. Glial cells as mediators of the effects of chronic cannabinoid exposure. Susceptibility to substance use disorders as outcome of maternal marijuana use.